MODEL FOR THE DEVELOPMENT AND DIAGNOSIS OF THE SENA ICT CREATIVITY LABORATORIO DE CREATIVIDAD TIC SENA - García Espinosa, Camilo Alejandro
This Article that analyzes the results of the quasi-experimental research of correlational scope developed by the author and developed with students of the SENA Center for Design and Industrial Technological Innovation (Colombia), raising the argumentative bases and reflection for the constitution of a model for the Development and diagnosis of the SENA ICT Creativity Laboratory. This model will allow also to analyze the impact of the development of creative skills on students and other collaborators based on the use of ICT tools, which is approached from three dimensions that are: psychosocial, environmental-pedagogical and environmental-physical. Each one of them will not only identify essential aspects for the implementation of a certain ICT tool, but also allow the identification and development of studies and researches that allow inferring in relation to the development of creative abilities of individuals as a result of the use of ICT tools.